MATHEMATICAL CONNECTION SKILLS IN PROBLEM SOLVING: THE ROLE OF COGNITIVE STYLES AMONG UPPER ELEMENTARY STUDENTS - Laili Nurul Azizah; Erry Hidayanto; Punaji Setyosari (Universitas Islam Negeri Mataram, 2025)
This study explores elementary students’ mathematical connection skills in solving problems based on their cognitive styles. A qualitative descriptive approach was employed to explain how reflective and impulsive students approach mathematical problem-solving. The research was conducted at SDN 4 Sumberbendo, Tulungagung, with 21 students initially tested using the Matching Familiar Figure Test (MFFT) to identify cognitive styles. This group selected six students (three reflective and three impulsive) as the primary subjects for detailed analysis. Data were collected through mathematical connection tests and semi-structured interviews, focusing on indicators of mathematising, representation, reasoning, communication, and strategy use. The findings reveal distinct differences between reflective and impulsive students. Reflective students demonstrated systematic and careful approaches, stronger skills in representation and reasoning, and better use of mathematical concepts such as least common multiples (LCM) and greatest common divisors (GCD). However, they often struggled to connect mathematical ideas with real-life contexts, such as percentage discounts or distribution problems. In contrast, impulsive students tended to answer quickly with less accuracy, often neglecting logical justification, although some succeeded in solving concrete problems like LCM tasks. Overall, the study highlights that cognitive styles significantly influence the quality of mathematical connections. The findings underscore the need for differentiated instructional strategies: reflective students should be supported to improve efficiency, while impulsive students require guidance to enhance accuracy and systematic reasoning.